Tetrazene–Characterization of Its Polymorphs - Jan Ryšavý; Robert Matyáš; Zdeněk Jalový; Jaroslav Maixner; Aleš Růžička; Stanislav Brandejs; Jiří Nesveda (Molecules, 2021)
The reinvestigation of tetrazene single crystalline material by means of X-ray methods resulted in a slightly different structure when compared to previously published data. Reaction conditions responsible for different crystalline modification formation were investigated. Newly described C form was found to be the primary reaction product and the combined action of temperature and the presence of water over time is required for the transition to the A form. Both forms were described by X-ray powder diffraction. Tetrazene was also subjected to infrared and Raman spectroscopy, which allowed differentiating between the forms. The molecule was isotopically labeled with 15N atoms at two different locations (ring and nitrogen sidechain) and employed in assigning vibrational modes to the resulting bands. Differences between sensitivities to mechanical stimuli of the two modifications were investigated and found industrially insignificant. In the same vein, the performance of either modification in primer composition and primer was identical.